QARAQALPAQ TILINDE KÓZ SOMATIZIMI - Umarova, Ú.A. (SCIENCE and SOCIETY, 2025)
This article uses proverbs and sayings from Karakalpak folklore using the somatism "Eye" as the main basis. It discusses proverbs and sayings rich in paremiology, concepts, and their specific characteristics.